2020
DOI: 10.1158/1078-0432.ccr-19-1623
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hypermutation and Defective Mismatch Repair in ctDNA from Metastatic Prostate Cancer

Abstract: Purpose: DNA mismatch repair defects (MMRd) and tumor hypermutation are rare and under-characterized in metastatic prostate cancer (mPC). Furthermore, because hypermutated MMRd prostate cancers can respond to immune checkpoint inhibitors, there is an urgent need for practical detection tools.Experimental Design: We analyzed plasma cell-free DNAtargeted sequencing data from 433 patients with mPC with circulating tumor DNA (ctDNA) purity !2%. Samples with somatic hypermutation were subjected to 185 Â whole-exome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 51 publications
(66 reference statements)
5
69
0
Order By: Relevance
“…In a retrospective study, MSI-H/dMMR mCRPC patients responded poorly to first-line treatment with abiraterone acetate or enzalutamide, with a median PFS of 9.9 months (15). Ritch et al reported that the median duration for first-line androgen receptor pathway inhibitor therapy was only 3.9 months in 11 dMMR patients (21). Our findings are highly consistent with these results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a retrospective study, MSI-H/dMMR mCRPC patients responded poorly to first-line treatment with abiraterone acetate or enzalutamide, with a median PFS of 9.9 months (15). Ritch et al reported that the median duration for first-line androgen receptor pathway inhibitor therapy was only 3.9 months in 11 dMMR patients (21). Our findings are highly consistent with these results.…”
Section: Discussionsupporting
confidence: 93%
“…A whole-exome analysis of 150 metastatic site biopsies from castration-resistant patients showed that 2.0% had aberrations in MSH2, and 0.7% had aberrations in MLH1 (20). A recent study identified 3.7% of metastatic prostate cancers with deleterious alterations in MSH2, MSH6, or MLH1 from cfDNA samples (21). Previous studies reported that dMMR prostate cancer is an aggressive disease with a higher Gleason score, lower differentiation, and a higher rate of distant metastasis (16,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…16 MMR have also been associated with aggressive features and more advanced disease at diagnosis. 34,35 However, conflicting results have been reported on the clinical outcomes of MMRdeficient prostate tumours. 34 While a study suggests favourable responses to ADT, others have found that MMR-deficient patients develop castration-resistant disease earlier than the MMRproficient ones.…”
Section: Genementioning
confidence: 99%
“…34 While a study suggests favourable responses to ADT, others have found that MMR-deficient patients develop castration-resistant disease earlier than the MMRproficient ones. 35,36 These differences in outcomes between studies may be related to the limited number of patients included and the different assays used to detect these alterations (targeted sequencing vs. immunohistochemistry). Further studies are needed to completely elucidate the clinical implications of these and other DDR alterations in prostate cancer.…”
Section: Genementioning
confidence: 99%
“…However, only a small proportion of prostate cancers exhibit dMMR, with estimates ranging from 3 to 8% (11)(12)(13)(14)(15). Thus, our best estimates of the efficacy of anti-PD1 therapy in dMMR or MSI-H prostate cancer are derived from retrospective case series with small numbers and short follow-up (15)(16)(17)(18)(19). More data are needed to define depth and durability of responses to anti-PD1 therapy for men with dMMR prostate cancer.…”
Section: Introductionmentioning
confidence: 99%